2022
DOI: 10.3389/fimmu.2022.877303
|View full text |Cite
|
Sign up to set email alerts
|

From COVID-19 to Sarcoidosis: How Similar Are These Two Diseases?

Abstract: Coronavirus disease 2019 (COVID-19), which is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), leads to the dysregulation of the immune system, exacerbates inflammatory responses, and even causes multiple organ dysfunction syndrome in patients with severe disease. Sarcoidosis is an idiopathic granulomatous multisystem disease characterized by dense epithelioid non-necrotizing lesions with varying degrees of lymphocytic inflammation. These two diseases have similar clinical manifestations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 143 publications
0
12
0
Order By: Relevance
“…It has been reported that alveolar macrophages from sarcoidosis patients secreted large amounts of CXCR3 ligands, including CXCL9, CXCL10, and CXCL11, that could play crucial roles in the accumulation of Tregs in the site of inflammation [ 65 , 66 ]. Similarly, the serum levels of CXCR3 ligands were also dramatically increased in sarcoidosis patients [ 67 , 68 , 69 ]. Furthermore, d’Alessandro et al noted an increased expression in Tregs of tissue-homing cell surface molecule CD103 that stimulated cell migration to inflamed mucosal tissues [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that alveolar macrophages from sarcoidosis patients secreted large amounts of CXCR3 ligands, including CXCL9, CXCL10, and CXCL11, that could play crucial roles in the accumulation of Tregs in the site of inflammation [ 65 , 66 ]. Similarly, the serum levels of CXCR3 ligands were also dramatically increased in sarcoidosis patients [ 67 , 68 , 69 ]. Furthermore, d’Alessandro et al noted an increased expression in Tregs of tissue-homing cell surface molecule CD103 that stimulated cell migration to inflamed mucosal tissues [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, the classical renin‐angiotensin system (RAS) (consisting of angiotensin converting enzyme (ACE), angiotensin II, and angiotensin II type 1 receptor (aT1R)) is negatively regulated by ACE2. SARS‐CoV has been shown to reduce pulmonary expression of ACE2 12 with the consequent hyperactivity of the RAS system postulated to contribute to the inflammatory response and cytokine storm seen in COVID‐19 lung disease 11 . Sarcoidosis is also associated with elevated circulating ACE levels 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarities in immune features of sarcoidosis and SARS‐CoV‐2 may potentially be indicative of a common pathophysiology that could explain their co‐existence. For example, the ‘cytokine storm’ seen in severe COVID‐19 pulmonary disease is characterized by elevated serum levels of a host of inflammatory cytokines, many of which are also upregulated in sarcoid lungs 11 . However, the majority of post‐COVID‐19 sarcoid‐like reactions reported have occurred in patients with mild disease.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al ( 46 ) identified several common clinical and immunological features between sarcoidosis and COVID-19.…”
Section: Immunopathological Considerationsmentioning
confidence: 99%
“…Moreover, an impaired function of Treg cells is also probably shared by both diseases, with a consequent role in amplifying immunoinflammatory response. COVID-19 and sarcoidosis share cytokine-releasing patterns: high levels of IL-6, IL-10, TNF-α, and IFN-γ are common in both diseases ( 46 ).…”
Section: Immunopathological Considerationsmentioning
confidence: 99%